A la caza de papeles olvidados : recuperando los protocolos de escribanos en el Archivo Notarial de Santa Fe de Antioquia (Colombia), 1630-1820 (2015)
ABSTRACT: November 2014 was the official start date for a project which aimed to recover, digitalize and index the oldest information conserved in the Archive of the Sole Notary of Santa Fe de Antioquia, Colombia. These are the oldest scribes' protocols still extant in the Department of Antioquia. This archive, on the point of disappearing, was literally forgotten. With the help of various institutions and individuals, we have managed to combine efforts to preserve it, and place its valuable resources at the service of users and researchers.